(untitled) (Research, Society and Development, 2022)
The production of digital content has gained increasing relevance in Brazil and worldwide and nurses have stood out in this scenario, especially within the social network Instagram®. Therefore, the aim of this study was to analyze and present the general content produced by nurses on the Instagram® social network. This is a qualitative study of direct observation in the Instagram® application of nurses’ profiles, carried out in October 2021. With the strategies and search engines, 105 nurses’ profiles resulted. After prior analysis and application of the inclusion and exclusion criteria, the sample consisted of 25 profiles. Among the main findings, 60% of the profiles analyzed had less than 10,000 followers and 36% had as their main scope the sharing of routines and study tips for nurses taking public exams and other course students’ area. Furthermore, 12% sought to share political content about the inclusion of nursing in political debates and valuing the profession. Therefore, Public profiles of nurses on Instagram® are used for a variety of professional purposes, all of them with great relevance for the propagation of content in the field of Nursing. Most of these profiles produce content for their own professional category. It is important that professional nurses can occupy these spaces of social media also to further provide the general population with health knowledge based on scientific evidence.